Research on Dynamic Characteristics of Flap Actuation System Considering Joint Clearance and Flexibility - Qi Wan; Geng Liu; Qi Liu; Ruiting Tong; Shangjun Ma (Machines, 2022)
The flight control effects and flight quality of the aircraft are influenced by the flap actuation system directly. The main motivation of this research is to develop a rigid-flexible model of the flap actuation system with clearance and to explore the coupling effects of clearance joints and flexible bodies on the system’s dynamic characteristics. A modified contact force model is used to a joint with small clearance, heavy load, and large contact area. Then, the effectiveness of an embedded modeling method of this modified model is verified. Based on this method, a rigid-flexible coupling model of the flap actuation system with multi clearance joints is established. Moreover, the influence of system parameters, such as clearance size and clearance joint position, and coupling effects of the flexibility and joint clearance on dynamic responses, are analyzed. The results show that: (1) flexible bodies act as a suspension to reduce negative effects of joint clearance on dynamic responses of a clearance-contained system; (2) one flexible body can reduce the oscillation phenomenon of joint clearances, yet the suspension effect will be gradually weaken with the increase of the clearance joint number; (3) coupling effects of the elastic deformation owing to multi flexible bodies and the collision interaction between multi clearance joints make the system tend to chaos, and the system stability is reduced. This study can contribute to predicting the collision characteristics of the aircraft transmission system and improving the transmission accuracy, response speed, and stability of the aircraft.